Single-step QuantiFERON screening of adult contacts: a prospective cohort study of tuberculosis risk. Issue 3 (6th September 2012) - Haldar, Pranabashis; Thuraisingam, Helen; Patel, Hemu; Pereira, Nelun; Free, Robert C; Entwisle, James; Wiselka, Martin; Hoskyns, Edwyn Wren; Monk, Philip; Barer, Michael R; Woltmann, Gerrit
Abstract : Background: The efffectiveness of tuberculosis (TB) contact screening programmes using interferon γ release assays remains uncertain as prospective contact TB risk is not well characterised. Objectives: To quantify 2-year TB risk and evaluate screening performance with single-step QuantiFERON TB Gold-In Tube (QFT) in adult contacts. To compare TB risk between QFT tested subgroups stratified by exposure type (smear positive pulmonary (SP) versus non-smear positive (NSP) TB) and age (younger (16–35 years) versus older (≥36 years)). Methods: Screening involved QFT testing in older contacts of SP and all younger contacts, 8–12 weeks after index notification. Chemoprevention (3RH) was offered to QFT positive (+) younger adults. TB risk was determined in a prospective cohort study. Results: 43 TB events occurred in 1769 adult contacts observed for median 717 days (2-year rate (95% CI)=2·5% (1.7 to 3.2)). Index-contact strain matching was demonstrable for 18 of 22 (82%) paired samples. No contacts (0/98) receiving 3RH developed TB. 215 of 817 appropriately tested adults (26.3%) were QFT+. 14 of 112 untreated QFT+ adults developed TB (2-year rate (95% CI)=13·4% (7.7 to 21.1)). The model required 35 contacts screened with QFT to identify one contact developing TB at 2 years. TB rates were comparable in QFT+ contacts of SP and NSP (rate ratio (RR)=0.98, p=0·962). For QFT+ older contacts, the disease rate was lower (8.9% (3.3 to 19.1)) and similar to the overall group rate (RR=1.4, p=0.503). Conclusions: QFT based single-step contact screening is effective in young adults.